2016
DOI: 10.1016/j.jrurstud.2016.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Why bother with Bere? An investigation into the drivers behind the cultivation of a landrace barley

Abstract: Why would the farmers in a developed, Western country, dominated by an industrialised agriculture, choose to grow a traditional crop variety? This study aimed to explore this question through an investigation of the reasons why a traditional landrace barley -known as Berewas still grown in the Scottish islands of Orkney and Shetland. Cultivated barley is one of the oldest and most widely grown cereals in the world and plays a significant role in global food security. However, since the beginning of the 20th ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…This difference in reported and observed susceptibility could be due to differences within the Bere population. Later interviews with farmers by Mahon et al (2016) suggest that Bere are more resistant to other foliar diseases, in particular rhynchosporium. This supports the suggestion that Bere barley is a prime source for resistance to rhynchosporium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference in reported and observed susceptibility could be due to differences within the Bere population. Later interviews with farmers by Mahon et al (2016) suggest that Bere are more resistant to other foliar diseases, in particular rhynchosporium. This supports the suggestion that Bere barley is a prime source for resistance to rhynchosporium.…”
Section: Introductionmentioning
confidence: 99%
“…This study investigates inherent resistance to rhynchosporium in Bere lines, as suggested by anecdotal evidence (Mahon et al 2016). Identifying individual lines that have high resistance along with associated genomic regions and candidate genes in these regions.…”
Section: Introductionmentioning
confidence: 99%
“…Important components of agrobiodiversity are landraces, i.e., local varieties of domesticated plant and animal species that have adapted to the natural and cultural local environment. Over the centuries landraces, based on traditional systems of production, ensured food and forage, minimized the production risk, stabilized yields [ 1 ], and favored low levels of technology and inputs [ 2 , 3 , 4 , 5 ]. Nowadays, landraces contribute to preserve social, cultural, health, recreational and identity values of community, so as to ensure wellbeing [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies suggest farmers' personal factors such as the farmers' ages (Negatu et al, 2016), household types (Chen et al, 2006), the family dependency ratio (Low, 1986) could all determine farmers' planting choices. Economic factors like the age-composition of the labor force (Greig, 2009), the agricultural income ratio (Arunrat et al, 2017), the characteristics of the market economy where farmers are willing to grow crops that have a predictable market price and are easy to sell (Jaffe, 1989;Haile et al, 2014;Wu et al, 2015;Mahon et al, 2016). Katundu et al (2014) showed that, in Tanzania, the lower input costs involved in the production of groundnut was the main driving force behind groundnut becoming the third most important crop.…”
Section: Introductionmentioning
confidence: 99%